Intervención cognitivo-conductual para el control de ansiedad ante la biopsia insicional en pacientes con cáncer de mama - Becerra Gálvez, Ana Leticia; Reynoso Erazo, Leonardo; García Rodríguez, Francisco Mario; Ramírez Ramírez, Armando (Psicooncología, 2016)
Oncological patients are submitted to invasive exams in order to obtain an accurate diagnosis; these procedures may cause maladaptative reactions (fear, anxiety and pain). Particularly in breast cancer, the most common diagnose technique is the incisional biopsy. Most of the patients are unaware about the procedure and for that reason they may focus their thoughts on possible events such as pain, bleeding, the anesthesia, or the later surgical wound care. Anxiety and pain may provoke physiological, behavioral and emotional complications, and because of this reason, the Behavioral Medicine trained psychologist takes an active role before and after the biopsy. The aim of this study was to evaluate the effect of a cognitive-behavioral program to reduce anxiety in women submitted to incisional biopsy for the first time. There were 10 participants from the Hospital Juárez de México, Oncology service; all of them were treated as external patients. The intervention program focused in psycho-education and passive relaxation training using videos, tape-recorded instructions and pamphlets. Anxiety measures were performed using the IDARE-State inventory, and a visual-analogue scale of anxiety (EEF-A), and the measurement of blood pressure and heart rate). Data were analyzed both intrasubject and intersubject using the Wilcoxon test (p≤0.05). The results show a reduction in anxiety (as in punctuation as in ranges) besides, a reduction in the EEF-A.
Keywords: Incisional biopsy; anxiety; cognitive-behavior therapy.